Treatment of Maisonneuve fractures using a plate, TightRope® syndesmosis fixation, and arthroscopic assistance - Puddu, Leonardo; Lugani, Giovanni; Segalla, Sara; Dorigotti, Andrea; Mercurio, Domenico; Santandrea, Alessandro; Cutaia, Rosario; Caggiari, Gianfilippo; Cortese, Fabrizio (Lo Scalpello - Journal, 2022)
Objective. To retrospectively evaluate short- and medium-term clinical and radiographic outcomes and the timing of return to sport in patients with Maisonneuve fractures treated in our operational unit by stabilization using a suture-button system and plate combined with arthroscopic assistance (SBPAA). Methods. Between January 2018 and December 2020, 8 patients took part in the study and underwent clinical and radiographic follow-up at 1, 3, 6, and 12 months during which we clinically re-evaluated the syndesmosis and determined values for tibiofibular overlap and medial clear space (MCS). Results. Patients returned to full weight-bearing walking on average in the ninth week and to sport in 7.5 months. Radiographic parameters continued to improve during follow-up. Two patients reported long-term complications (residual joint stiffness and complex regional pain syndrome). Conclusions. Despite the limitations due to the small number of patients, this study highlights the importance of intraoperative arthroscopy in recognizing and treating associated osteochondral lesions and enabling proper evaluation of the syndesmosis. In addition, the combination of robustness and elasticity provided by the use of a double TightRope and plate mimics the normal anatomy of the syndesmosis and guarantees a rapid return to sporting activity.